2006
DOI: 10.1606/1044-3894.3578
|View full text |Cite
|
Sign up to set email alerts
|

Informing Best Practices for Children in Psychiatric Crises: Perspectives and Insights from Families

Abstract: Young children in psychiatric crisis present complex challenges to their families and service providers. This article presents a qualitative study of families' perspectives on the crisis that led to their child's hospitalization, as well as their experience and satisfaction with prior communitybased services including crisis services. Results of the study support the usefulness of an ecological view on child mental health emergencies, and specify the need for the development of a more family-centered, communit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(22 citation statements)
references
References 18 publications
0
22
0
Order By: Relevance
“…For the research studies, there were 31 quantitative studies (reported across 37 reports 32,34,57-69,71-75, 77-89,92,93,98,132 ) and 11 qualitative studies. 70,76,90,91,[94][95][96][97]99,100,133 The quantitative studies included a prospective cohort study (n = 132), retrospective cohort studies (n = 12 34,62,[65][66][67][68]71,72,74,75,87,89 ), quasi-experimental studies (four studies across six reports 82,83,86,92,93,132 ), randomised controlled trials (RCTs) (four studies across eight reports 57,61,64,[78][79][80][81]84 ) and descriptive cross-sectional studies (n = 10 58-60, 63,69,73,77,85,88,98 ).…”
Section: Study Designs and Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For the research studies, there were 31 quantitative studies (reported across 37 reports 32,34,57-69,71-75, 77-89,92,93,98,132 ) and 11 qualitative studies. 70,76,90,91,[94][95][96][97]99,100,133 The quantitative studies included a prospective cohort study (n = 132), retrospective cohort studies (n = 12 34,62,[65][66][67][68]71,72,74,75,87,89 ), quasi-experimental studies (four studies across six reports 82,83,86,92,93,132 ), randomised controlled trials (RCTs) (four studies across eight reports 57,61,64,[78][79][80][81]84 ) and descriptive cross-sectional studies (n = 10 58-60, 63,69,73,77,85,88,98 ).…”
Section: Study Designs and Methodsmentioning
confidence: 99%
“…• CYP experiencing, or who had experienced, a crisis (31 studies across 34 reports 32,34,[58][59][60][61][62][63][65][66][67][68][69][70][71][72][73][74][75]77,[82][83][84]86,87,89,[91][92][93][94][95]97,98,100,132 ) • CYP experiencing crisis and their family members (two studies across six reports 57,64,[78][79][80][81] • family members/parents of CYP experiencing crisis (n = 2 76,88 )…”
Section: Participant Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The full-data extraction and thematic summaries can be found in Appendix S10. Five services in which crisis care for CYP was provided did not present any details of their goals (Bolger et al, 2004;Idenfors et al, 2015;Liegghio & Jaswal, 2015;Nirui & Chenoweth, 1999;Walter et al, 2006). Seven distinct goals of crisis services were described across the included literature.…”
Section: Objective 4: Goals Of Crisis Interventionsmentioning
confidence: 99%
“…Encouraging creativity, or being playful, in family therapy is a key ingredient in attachment building among family members (Creed & Kendall, 2005; Gil, 1994; Walter & Petr, 2006). Attachment injuries can occur through family difficulties adjusting to child illness or mental illness, damaging secure relationships (Cloutier, Manion, Walker, & Johnson, 2002).…”
Section: Components and Rationale For Real Therapymentioning
confidence: 99%